Communication Modes and Functions in Children With Cerebral Palsy - McFadd, Emily D. (J Speech Lang Hear Res, 2020)
PURPOSE: This study seeks to determine how speech-language impairments relate to the frequency and diversity of communication modes and functions produced by children with cerebral palsy (CP) during interactions with their mothers. METHOD: We studied 40 children with CP (M (age) = 62 months) comprising three groups: those who were unable to speak and had anarthria (n = 15), those with speech motor impairment and language comprehension impairment (SMI-LCI; n = 15), and those with speech motor impairment and typical language comprehension (SMI-LCT; n = 10). Mother–child play interactions were coded for child modes and functions. Generalized linear regression models were used to examine the relationship between profile group and frequencies of communication modes and functions. RESULTS: Results indicated groups SMI-LCI and SMI-LCT had significantly higher mean frequencies of vocalizations, vocalizations + gestures, comments, initiations, and requests than the group of those who were unable to speak and had anarthria. All children used vocalizations primarily, though these vocalizations were often not understood. SMI-LCI and SMI-LCT differed on two measures: frequency of gestures and frequency of initiations. The majority of children in this sample did not have access to augmentative and alternative communication devices. CONCLUSION: Results of this study highlight the need for parent-mediated interventions for children with CP that emphasize multimodal communication tailored to impairment profiles. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.12354704